The Growing Gap Between Pioneers and Laggards: Digitalization, automation, and organizational change in the wake of the COVID-19-crisis in Germany - Martin Krzywdzinski; Florian Butollo; Jana Flemming; Christine Gerber; David Wandjo; Nina Delicat; Lorena Herzog; Marc Bovenschulte; Michael Nerger (Weizenbaum Institute for the Networked Society - The German Internet Institute, 2022)
The COVID 19 crisis has had a massive impact on the world of work. Based on a standardized survey of 540 company sites and 34 qualitative case studies in six industries (automotive, chemicals, mechanical engineering, logistics, healthcare and financial services), this study examines how companies' digitalization and automation strategies have changed in the context of the pandemic. The analysis shows that the companies surveyed have by and large coped well with the crisis. However, an increasing polarization is becoming apparent. Digital pioneers intensified digitalization measures to a greater extent than those that were already behind in this respect before the pandemic. The focus of digitalization during the pandemic was particularly on supporting processes in administration, human resources management and sales. Automation also primarily played a role in these fields and only a minority of respondents expected employment losses in the medium term. Another key finding of this study is the correlation between technical and organizational innovation. It can be observed that those companies that invested more heavily in technical digitalization processes were also more inclined to make organizational changes with regard to management styles, working hours and work organization.
Additional information: This work has been funded by the Federal Ministry of Labour and Social Affairs (684 11 - "Denkfabrik Digitale Arbeitsgesellschaft") and the Federal Ministry of Education and Research of Germany (BMBF) (grant no.: 16DII121, 16DII122, 16DII123, 16DII124, 16DII125, 16DII126, 16DII127, 16DII128 - "Deutsches Internet-Institut").
Keywords: 330; Bundesrepublik Deutschland; soziotechnisches System; Arbeitszeitflexibilität; Arbeitswelt; Digitalisierung; Epidemie; COVID-19; Krisenmanagement; Automatisierung; Unternehmensführung; organisatorischer Wandel; Führungsstil; Arbeitsorganisation